Investigation of Taylor-Görtler-like Vortices Using the Parallel Consistent Splitting Scheme (Advances in Applied Mathematics and Mechanics, 2021)
Symmetric Taylor-Görtler-like vortices at $Re$=3200 and 5000 in 3D rectangularcavities with a moving top lid are studied numerically and tested with aspanwise aspect ratio of 1 : 1 : $L$, where $L$=1, 2, 3. Solutions are obtained by solvingthe momentum equations and the continuity equations using the consistentsplitting scheme. The code presented here was ported to the Parallel InteroperableComputational Mechanics System Simulator (PICMSS). Stable solutions areobtained as limit cases of the transients.